Does servant leadership moderate the link between strategic human resource management on rule breaking and job satisfaction? - Zafer Adiguzel; Mehmet Faruk Ozcinar; Himmet Karadal (European Research on Management and Business Economics, 2020)
In today’s competitive environment and global world, where the boundaries have disappeared as a result of the continuous development in communication and technology, the attitudes and behaviours of the employees in their organisations are becoming more important in terms of employees’ performance, strategic human resources management (SHRM), leadership roles of senior managers. In this study, the effects of (SHRM) and servant leadership on ‘rule breaking’ behaviours and ‘job satisfaction’ of the employees in their organisation have been examined. Our findings and analyses show that private organisations are afraid of losing customers in competitive environments and therefore their employees go beyond the determined procedures to sustain the interests of their organisation. Future studies should focus on the attitudes and behaviors of individuals in order to develop new theoretical concepts and better studies related to human resources and leadership styles. The sample population of our study consists of 385 white-collar employees working in the public and private sectors in the Central Anatolia region. 228 were employed in the private sector and 157 in the public sector. Findings were subjected to factor and reliability analyses using SPSS AMOS 22 program, hypotheses were tested by regression analysis and the results were analysed and evaluated.